Further development of the attitude difference method for estimating deflections of the vertical in real time. (2nd June 2016) - Zhu, Jing; Zhou, Zebo; Li, Yong; Rizos, Chris; Wang, Xingshu
Abstract: An improvement of the attitude difference method (ADM) to estimate deflections of the vertical (DOV) in real time is described in this paper. The ADM without offline processing estimates the DOV with a limited accuracy due to the response delay. The proposed model selection-based self-adaptive delay feedback (SDF) method takes the results of the ADM as the a priori information, then uses fitting and extrapolation to estimate the DOV at the current epoch. The active region selection factor F th is used to take full advantage of the Earth model EGM2008 and the SDF with different DOV exhibitions. The factors which affect the DOV estimation accuracy are analyzed and modeled. An external observation which is specified by the velocity difference between the global navigation satellite system (GNSS) and the inertial navigation system (INS) with DOV compensated is used to select the optimal model. The response delay induced by the weak observability of an integrated INS/GNSS to the violent DOV disturbances in the ADM is compensated. The DOV estimation accuracy of the SDF method is improved by approximately 40% and 50% respectively compared to that of the EGM2008 and the ADM. With an increase in GNSS accuracy, the DOV estimation accuracy could improve further.